Towards Universal Health Care Coverage : Goal-oriented Framework for Policy Analysis - Kutzin, Joseph (World Bank, Washington, DC, 2013)
Universal coverage with the health care insurance function may be defined as physical and financial access to necessary health care of good quality for all persons in a society. It implies protection against the risk that if expensive (relative to an individual's or family's means) health care services are needed, services of adequate quality will be physically accessible, and the costs of these services will not prevent persons from using them or impoverish their families. Defined in this way, the extent of protection is an important determinant of performance vis-a-vis broad health and social welfare policy objectives, because it entails quality of care (a means for improving the health status of the population), equity in access to effective care (a means to reduce inequality in health status), and protection against the risk of impoverishment as a consequence of health care costs. This paper was motivated by the perception that, with respect to health care financing, there is frequently confusion between policy tools and policy objectives. The paper emphasizes the importance of distinguishing between the ends and means of health policy in general, and of health insurance in particular.